Incarcerated Body and Political Self in Tek Nath Rijal’s Torture Killing Me Softly: Bhutan Through the Eyes of Mind Control Victim - Dangaura, Mohan (Mindscape: A Journal of English & Cultural Studies, 2023)
Tek Nath Rijal’s prison narrative Torture Killing Me Softly: Bhutan Through the Eyes of Mind Control Victim narrates the story of a Bhutanese captive in one’s own state. The prison narrative describes the holocaust-type imprisoned life and state tortured politically willed refugee. The captive accuses the state for secretly monitoring, and manipulating his state of mind through some highly sophisticated, lethal and anti-human ultra-modern “Mind Control Machine” (specific title is unavailable in the narratives). Adds on, the captive is seen to be fighting with his state-owned body’s involuntary actions through his own body’s voluntary conscience. The fight between voluntarily and involuntarily controlled self becomes so confusing that it brings readers doubt his objective narration. As the sociologist Anthony Giddens concerns that in the time of high modernity individuals reflect on their self-body to define the reliable sense of identity and sane-self, the captive’s narration attempts to justify the his sanity and ‘politically correct self’. The captive’s allegation on the machine-technology for reconstructing his body restrains him into a controlled and split subject.